(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Le sfide del nuovo multiculturalismo in materia matrimoniale - 2. La riforma del processo matrimoniale canonico e le sue potenziali ricadute sul giudizio di delibazione - 3. Il processus brevior - 4. La crisi della bilateralità - 5. Il “mite” pluralismo statunitense e le nuove “anti-sharia laws” - 6. L’esperienza del pluralismo “forte” israeliano e i suoi effetti sulle minoranze - 7. Modelli di pluralismo a confronto. Pluralism in Marriage: the New Challenges of the “Overlapping Jurisdictions” ABSTRACT: The challenges of the “new multiculturalism” in the field of marriage law regard not only which forms of marriage should be recognized by the State but also the forums in which marriage cases can be adjudicated and the role of faith-based laws and religious courts in democratic and secular legal systems. Religious groups increasingly ask for accommodation of their cultural identities; however, a growing skepticism concerning forms of religious jurisdiction is developing in regimes devoted to individual liberties, which employ public policy as grounds to vacate religious rulings. The present paper highlights the need for Western States to update and exploit the full potential of their legal instruments in order to prevent restrictions on collective and individual religious freedom in matters of marriage.